57.7k views
3 votes
4x – 3y=8
2. 5x – 2y = -11

1 Answer

1 vote

Answer:


x = -7


y = - 12

Explanation:

The given system is:

4x-3y=8

5x-2y=-11

We make x the subject in the top equation to get:


x = (3)/(4)y + 2

Plug this expression for x in the bottom equation to get


5( (3)/(4)y + 2) - 2y= - 11

We expand to obtain


(15)/(4) y + 10 - 2y = - 11

Multiply through by 4


15y + 40 - 8y = - 44

Group similar terms


15y - 8y = - 44 - 40


7y = - 84


y = - (84)/(7) =-12

This means


x = -12* (3)/(4) + 2


x = - 7

User Sayed
by
5.5k points